Radiolabeled Monoclonal Antibody Against Colony-Stimulating Factor 1 Receptor Specifically Distributes to the Spleen and Liver in Immunocompetent Mice - Waaijer, Stijn J. H.; Suurs, Frans V.; Hau, Cheei-Sing; Vrijland, Kim; de Visser, Karin E.; de Groot, Derk Jan A.; de Vries, Elisabeth G. E.; Lub-de Hooge, Marjolijn N.; Schröder, Carolina P. (Frontiers in Oncology, 2021)
Macrophages can promote tumor development. Preclinically, targeting macrophages by colony stimulating factor 1 (CSF1)/CSF-1 receptor (CSF1R) monoclonal antibodies (mAbs) enhances conventional therapeutics in combination treatments. The physiological distribution and tumor uptake of CSF1R mAbs are unknown. Therefore, we radiolabeled a murine CSF1R-mAb and preclinically visualized its biodistribution by positron emission tomography (PET). CSF1R-mAb was conjugated to N-succinyl-desferrioxamine (N-suc-DFO) and subsequently radiolabeled with zirconium-89 (89Zr). Optimal protein tracer dose was first determined in non-tumor-bearing mice to assess physiological distribution. Next, biodistribution of optimal tracer dose and 89Zr-labeled isotype control were compared with PET and ex vivo biodistribution after 24 and 72 hours in mammary tumor-bearing mice. Tissue autoradiography and immunohistochemistry determined radioactivity distribution and tissue macrophage presence, respectively. [89Zr]Zr-DFO-N-suc-CSF1R-mAb optimal protein dose was 10 mg/kg, with blood pool levels of 10±2 % injected dose per gram tissue (ID/g) and spleen and liver uptake of 17±4 and 11±4 %ID/g at 72 hours. In contrast, 0.4 mg/kg [89Zr]Zr-DFO-N-suc-CSF1R-mAb was eliminated from circulation within 24 hours, spleen and liver uptake were 126±44 % and 34±7 %ID/g, respectively. Tumor-bearing mice showed higher uptake of [89Zr]Zr-DFO-N-suc-CSF1R-mAb in liver, lymphoid tissues, duodenum, and ileum, but not in tumor compared to 89Zr-labeled control at 72 hours. Immunohistochemistry and autoradiography showed 89Zr was localized to macrophages within lymphoid tissues. Following [89Zr]Zr-DFO-N-suc-CSF1R-mAb administration, tumor macrophages were almost absent, whereas isotype tumors contained over 500 cells/mm2. We hypothesize that intratumoral macrophage depletion by [89Zr]Zr-DFO-N-suc-CSF1R-mAb precluded tumor uptake higher than 89Zr-labeled control. Translation of molecular imaging of macrophage targeting therapeutics to humans may support macrophage-directed therapeutic development.